ASSESSMENT OF GOING CONCERN IN AUDIT ENGAGEMENTS - Mamatov Khabibulla Mamatovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines the methodological aspects and practical challenges associated with the auditor’s assessment of the going concern assumption in audit engagements. The going concern principle represents a fundamental basis for the preparation of financial statements, and its proper evaluation is critical for ensuring the reliability of financial reporting. The study identifies key risk factors, including liquidity problems, excessive leverage, operating losses, and external economic instability, which may cast significant doubt on an entity’s ability to continue as a going concern. Based on International Standards on Auditing (ISA 570) and empirical analysis, an improved methodological framework for evaluating going concern risk, collecting audit evidence, and enhancing disclosure quality is proposed. The findings contribute to improving audit quality and strengthening stakeholders’ confidence in financial statements.